Systematic review with meta‐analysis: cholecystectomy for biliary dyskinesia—what can the gallbladder ejection fraction tell us? - Gudsoorkar, Vineet S.; Oglat, Ayah; Jain, Amita; Raza, Ali; Quigley, Eamonn M. M. (Alimentary pharmacology & therapeutics, 2019)
Summary Background Gallbladder dyskinesia (gallbladder spasm, biliary dyskinesia or chronic acalculous cholecystitis) is a poorly defined entity which presents as biliary‐type pain without any identifiable organic pathology. Abnormal gallbladder ejection fraction (GBEF) is used by some to select those likely to benefit from cholecystectomy. The validity of this approach has been questioned. Aim To systematically review the literature and summarise the evidence surrounding the practice of cholecystectomy based on GBEF for gallbladder dyskinesia. Methods We conducted a systematic search of PubMed/MEDLINE and SCOPUS from 1980 to 2016 to identify the relevant literature. Results Twenty‐nine studies including 2891 patients were included in the final analysis. In comparing cholecystectomy with medical management, patients with a normal GBEF did not benefit from cholecystectomy; whereas those with low GBEF had a higher chance (RR, relative risk = 2.37) of symptomatic improvement following surgery. When those classified as “low” and “normal” GBEF were compared in terms of outcome following cholecystectomy, the rate of improvement following surgery was similar in the two groups (RR 1.09) which suggests a placebo effect of surgery. Conclusions While a low GBEF may provide some guidance in identifying those with gallbladder dyskinesia who may benefit from cholecystectomy, the available data are inconsistent and based on studies of poor quality which are often subject to bias and the impact of confounding factors. For these reasons, we conclude that the role of scintigraphy and cholecystectomy in the definition and management of this disorder remain unclear pending definitive study.